A paradigm shift in clinical nutrition. Issue 3 (March 2023) - Cardenas, Diana; Ochoa, Juan B.
Summary: The current clinical nutrition paradigm is that decreased caloric intake, resulting in a caloric deficit, is central to the development disease-related malnutrition (DRM). In following with this paradigm, one should assume that nutrition interventions with artificially administered nutrition (food substitution paradigm) aimed at preventing a caloric deficit should result in the prevention and/or successful treatment of DRM. However, clear evidence demonstrates that the DRM observed in diverse illnesses is at least partially resistant to nutrition interventions aimed at preventing the development of a caloric deficit. Simply put, DRM cannot be prevented nor resolved through a nutrition intervention aimed solely on replacing what the person cannot or will not eat. It is time to stop oversimplifying nutrition therapy in clinical nutrition interventions as a food substitution issue, focusing instead on developing and testing innovative hypotheses aimed at a mechanistic understanding of how DRM develops. Through this effort, new paradigms should evolve. The aim of this opinion paper is to provide an overview of why we need a shift in the current paradigm.